1995
DOI: 10.1038/bjc.1995.423
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of temozolomide-induced cytotoxicity: a comparative study of the biological effects of poly(ADP-ribose) polymerase inhibitors

Abstract: Summary Four poly(ADP-ribose) polymerase (PADPRP) inhibitors [3-aminobenzamide, benzamide, 3,4-dihydro-5-methoxyisoquinolin-1(2H)-one (PD 128763) and 8-hydroxy-2-methylquinazolin-4(3H)-one (NU1025)] were compared with respect to their effects on a number of biological end points. The following parameters were assessed: their ability to inhibit the enzyme in permeabilised L1210 cells; their ability to potentiate the cytotoxicity of temozolomide (including the cytotoxicity of the compounds per se); their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
79
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 27 publications
8
79
0
Order By: Relevance
“…NU1025 was not cytotoxic per se at 200 µM (% survival for a 16-h exposure was 100 ± 12%), consistent with the results from the previous study by Boulton et al (1995). Exposure to the topoisomerase I and II inhibitors camptothecin and etoposide for 16 h induced a concentration-dependent decrease in L1210 cell survival ( Figure 1A and 1B).…”
Section: Potentiation Of Camptothecin and Etoposide Cytotoxicity By Nsupporting
confidence: 90%
See 1 more Smart Citation
“…NU1025 was not cytotoxic per se at 200 µM (% survival for a 16-h exposure was 100 ± 12%), consistent with the results from the previous study by Boulton et al (1995). Exposure to the topoisomerase I and II inhibitors camptothecin and etoposide for 16 h induced a concentration-dependent decrease in L1210 cell survival ( Figure 1A and 1B).…”
Section: Potentiation Of Camptothecin and Etoposide Cytotoxicity By Nsupporting
confidence: 90%
“…Data, expressed as rad equivalents, from three independent experiments are given in Table 2. No DNA strand breakage was detected following exposure to 200 µM NU1025 alone (Figure 2A and 2B), consistent with the observation that exposure of cells to 1 mM NU1025 for 24 h had no effect on DNA strand-break levels (Boulton et al, 1995). Although exposure to an LC 50 concentration of camptothecin (15 nM) did not induce significant levels of DNA strand breaks, compared to control cells, treatment with 40 nM camptothecin (an LC 90 concentration) did produce a significant level of breaks ( Figure 2A, Table 2).…”
Section: Potentiation Of Camptothecin and Etoposide Cytotoxicity By Nsupporting
confidence: 88%
“…While AGT depletion has been widely shown to potentiate the cytotoxicity of both methylating and bifunctional chloroethylating agents, studies investigating PARP inhibition and cytotoxicity have predominantly focused upon methylating agents such as dimethyl sulphate (Durkacz et al, 1980), N-methyl-N'-nitro-N-nitrosoguanidine (Nduka et al, 1980) and temozolomide (Boulton et al, 1995). Although it has been suggested that the enhancement of BCNU cytotoxicity by the nucleoside analogue tiazofurin is related to the inhibition of PARP activity , an additional study has indicated that the cytotoxicity of the bifunctional nitrosoureas is unaffected by PARP inhibition (Sebolt-Leopold and Scavone, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…An effect on ADP(ribose) metabolism is most probable, given that 3-AB (1 mM) can completely inhibit a Potentiation of temozolomide by O6-BG and 3-AB SR Wedge et al 1034 50% reduction in cellular NAD produced by treatment with 2 mM temozolomide (Boulton et al, 1995). The association between DNA strand breakage and the inhibition of PARP with 3-AB, however, remains controversial (Boulton et al, 1995), and it is possible that the enhancement of temozolomide cytotoxicity by 3-AB could be related to the inhibition of acceptor protein ADP-(ribosyl)ation, particularly if such proteins regulate cell cycle progression or apoptosis in response to DNA damage (Kastan et al, 1991;Nosseri et al, 1994;Malcomson et al, 1995). The magnitude by which methylation and chloroethylation cytotoxicity was enhanced by 06-BG did not clearly correlate with AGT activity, although resistance to both agents can be multifactorial and dependent on factors other than at the level of DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…most of which has-e investigated the potentiation of monofunctional alkylatina agents and ionizing, radiation as these therapies are the most potent actixators of PARP. althoug!h some other agents have also been evaluated (reviewed in Griffin et al 1995).…”
mentioning
confidence: 99%